PSYCHOSPIRITUAL ASSISTANCE MODEL FOR ELEMENTARY SCHOOL CHILDREN TO IMPROVE MENTAL WELFARE IN THE TALLUNGLIPU CONGREGATION ENVIRONMENT - Lura, Hans; Sampelolo, Rigel (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This study addresses the critical issue of mental health among elementary school students at Dasar School, a factor that significantly impedes their academic and social development within the Tallunglipu Congregation community. Faced with various psychological challenges, these children require specialized interventions. This research aims to develop a psychospiritual counseling model tailored to the unique needs and context of elementary school students to enhance their mental well-being. The primary objective is to document the psychological experiences and changes in children following their participation in a program that integrates mindfulness and spiritual practices. Utilizing a qualitative case study design, data was collected through direct observation of counseling activities, process documentation, and interviews with students, teachers, and other relevant individuals. Thematic analysis was employed to identify socio-emotional changes and assess the role of counseling in improving children's mental health. Findings indicate that psychospiritual counseling effectively promotes emotional regulation and a sense of calm among the students. Children demonstrated increased resilience, improved stress management, and a greater capacity for developing harmonious interpersonal relationships. Both students and teachers reported notable improvements, including enhanced patience and increased motivation for learning. Furthermore, students were better able to grasp the lessons and values embedded within spiritual teachings. While challenges such as variations in student concentration during sessions were observed, these were mitigated through intensive guidance. The results confirm that the psychospiritual counseling model is an effective intervention for improving the mental health of children within the Tallunglipu Congregation. This program serves as a viable, context-specific intervention rooted in religious and spiritual principles, and it can be integrated into the character development curriculum at the elementary school level.